2010
DOI: 10.1016/s1473-3099(10)70222-x
|View full text |Cite|
|
Sign up to set email alerts
|

Causes of encephalitis and differences in their clinical presentations in England: a multicentre, population-based prospective study

Abstract: The Policy Research Programme, Department of Health, UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

55
986
11
73

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,178 publications
(1,125 citation statements)
references
References 32 publications
55
986
11
73
Order By: Relevance
“…While HSV-2 is also capable of causing encephalitis (particularly in the immunocompromised host), HSV-1 is responsible for~90 % of HSV encephalitis in adults and children, and is the focus of this review [41]. Despite only rarely manifesting as encephalitis in infected individuals, HSV-1 is consistently the single most common cause of sporadic encephalitis worldwide [42][43][44][45][46][47][48][49][50][51][52]. The incidence of HSVE worldwide is estimated to be between 2 and 4 cases/1,000,000 [44], and the incidence in the USA is similar [53].…”
Section: Epidemiologymentioning
confidence: 99%
“…While HSV-2 is also capable of causing encephalitis (particularly in the immunocompromised host), HSV-1 is responsible for~90 % of HSV encephalitis in adults and children, and is the focus of this review [41]. Despite only rarely manifesting as encephalitis in infected individuals, HSV-1 is consistently the single most common cause of sporadic encephalitis worldwide [42][43][44][45][46][47][48][49][50][51][52]. The incidence of HSVE worldwide is estimated to be between 2 and 4 cases/1,000,000 [44], and the incidence in the USA is similar [53].…”
Section: Epidemiologymentioning
confidence: 99%
“…2,3 A recent study suggested that Nmethyl-D-aspartate receptor antibody (NMDAR-Ab) encephalitis, the bestknown autoimmune form, is more common than herpes simplex virus (HSV) encephalitis in children and young adults, 4 and a prospective study of adults (n = 134) and children (n = 69) with encephalitis found that infectious encephalitis and immunemediated forms were identified in 42% and 21% of the cohort, respectively. 5 However, most of the previous larger studies of encephalitis in children were undertaken before the advent of neuronal autoantibody testing. [6][7][8] We studied clinical and radiologic features, serum autoantibodies in acute archived samples, and longterm outcomes in a large retrospective cohort of pediatric encephalitis from a single center.…”
Section: What This Study Addsmentioning
confidence: 99%
“…complex and the N-methyl, D-aspartate (NMDA) receptor [3][4][5][6] . These antibodies are likely to be pathogenic, the diseases are typically immunotherapy-responsive, and they are only associated with cancer in a minority of patients.…”
mentioning
confidence: 99%